The History of a Pinus Stand on a Bog Degraded by Post-War Drainage and Exploitation in Southern Poland - Anna Cedro; Bernard Cedro; Katarzyna Piotrowicz; Anna Hrynowiecka; Tomasz Mirosław Karasiewicz; Michał Mirgos (Applied Sciences)
A dendrochronological study was conducted on a submontane raised bog, Bór na Czerwonem, in the Orava–Nowy Targ Basin in Southern Poland. In the past, the bog was drained to enable peat extraction. In recent years, a number of measures considered as active protection were undertaken, including the construction of ridges and locks, filling of the drainage trenches, and clearance of most of the tree stand on the bog dome. Pinus sylvestris, P. × rhaetica, and P. mugo were the focuses of the study, which aimed to determine the age of the genus stand and its age structure and to identify the factors influencing tree ring width. The age of the trees indicates a post-war succession induced by large-scale drainage in 1942, although single trees were present on the bog dome as early as the late 19th century, and probably earlier. High values of pith eccentricity at ground level testify to substratum instability and the impact of strong winds on tree ring formation. The growth–climate relationships change with the progressive climate change: the significance of insolation increases, while the significance of the absolute air temperature decreases. The thermal and pluvial conditions of the summer in the previous growth season, however, make the strongest impact on the tree ring width in the following growth season. The health of the trees left growing on the bog, due to the constantly rising water level, will likely deteriorate, and a decreasing number of seedlings will be observed. A full assessment of the conducted restoration efforts, however, will be possible after years of monitoring of the bog environment.